Factors affecting premature browning in cooked ground beef - Melvin C. Hunt; K.E. Warren; Donald H. Kropf; M.A. Hague; C.L. Waldner; Sally L. Stroda; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1995)
Some ground beef patties developed an internal, brown cooked color and looked well-done at temperatures as low as 13 1EF, whereas normal patties were re d to pink. The premature brown color was not relate d to percent fat; patty compaction; animal source and maturity; pH (5.5 to 5.8); or concentrations of raw patty heme and nonhemeiron, myoglobin, and total pigment. Because oxidation-reduction potential and total reducing activities were higher (P<.05) and TBA numbers were lower (P<.05) in normal than prematurely brown patties, the brown color is apparently related to greater patty oxidation.
Keywords: Cattlemen' s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Ground beef; Cooked color; Oxidation; Reducing activity; Food safety